Sleep disturbances and sleep patterns in children with tic disorder: A case-control study - Mi, Yunhui; Zhao, Runzhi; Sun, Xiaoning; Yu, Pingbo; Wang, Wenqin; Li, Jijun; Liang, Zhenwen; Wang, Hui; Wang, Guanghai; Sun, Kexing (Frontiers in Pediatrics, 2022)
Study Objectives: To characterize sleep disturbances and sleep patterns in children with Tic disorder (TD), and explore their association with TD severity and types. Methods: A case-control study was conducted in 271 children with TD recruited from a clinical setting and 271 non-TD children recruited from a primary school, matched by age (mean=8.47 years, SD=1.53 years) and gender (15.1% female). The Children's Sleep Habits Questionnaire (CSHQ) was used to assess sleep patterns and sleep disturbances. The TD types and severity were assessed with the Yale Global Tic Severity Scale (YGTSS). Results: The TD children scored higher on CSHQ total score than non-TD group (t=29.50, p<0.001) and demonstrated severer global sleep disturbance. Compared to non-TD children, TD children presented with increased risks for global sleep disturbance (aOR:1.95;95%CI=1.20-3.06), and most specific sleep disturbances, including bedtime resistance (aOR:3.15;95%CI=1.96-5.06), sleep onset delay (aOR:3.43;95%CI=1.58-7.46), sleep anxiety (aOR:2.83;95%CI=1.83-4.38), parasomnias (aOR:3.68;95%CI=2.02-6.62), night waking (aOR:9.29;95%CI=2.64-32.65), sleep disordered breathing (aOR:1.72;95%CI=1.03-2.90) and daytime sleepiness (aOR:1.72; 95%CI=1.09-2.74). Children with mild and moderate tics, Provisional Tic Disorder (PTD), Chronic Tic Disorder (CTD) and Tourette Syndrome (TS) presented with more global and more specific sleep disturbances. In addition, combined ADHD etc. Conclusion: Children with TD are major risks for increased sleep disturbances, especially for those with severe and chronic symptoms. Furthermore comorbid ADHD increases risk in certain areas of sleep. These findings highlight the importance to consider sleep outcomes in the assessment and treatment for children with TD.